SVG essentials - Eisenberg, J. David (O'Reilly, 2002)
Scalable Vector Graphics -- or SVG -- is the new XML-based graphics standard from the W3C that will enable Web documents to be smaller, faster and more interactive. J. David Eisenberg's insightful book takes you through the ins and outs of SVG, beginning with basics needed to create simple line drawings and then moving through more complicated features like filters, transformations, and integration with Java, Perl, and XSLT. Unlike GIFs, JPEGs or PNGs (which are bitmapped), SVG images are both resolution- and device-independent, so that they can scale up or down to fit proportionally into any size display or any Internet device -- from PDAs to large office monitors and high-resolution printers. Smaller than bitmapped files and faster to download, SVG images can be rendered with different CSS styles for each environment. They work well across a range of available bandwidths. SVG makes it possible for designers to escape the constant need to update graphics by hand or use custom code to generate bitmap images. And while SVG was created with the Web in mind, the language has a variety of other uses. SVG greatly simplifies tasks like: Creating web sites whose graphics reflect the content of the page, changing automatically if the content changes Generating graphs and charts from information stored in a wide variety of sources Exchanging detailed drawings, from architectural plans to CAD layouts to project management diagrams Creating diagrams that users can explore by zooming in and panning around Generating bitmap images for use in older browsers using simple automatable templates Managing graphics that support multiple languages or translations Creating complex animationBy focusing sharply on the markup at the foundation of SVG, SVG Essentials gives you a solid base on which to create your own custom tools. Explanations of key technical tools -- like XML, matrix math, and scripting -- are included as appendices, along with a reference to the SVG vocabulary. Whether you're a graphic designer in search of new tools or a programmer dealing with the complex task of creating and managing graphics, SVG Essentials provides you with the means to take advantage of SVG